The Role of Pancasila Education Teachers in Building Student Creativity through Deep Learning (Case Study at SMA Negeri 12 Semarang) - Dimas Eka Priambudi; Novia Wahyu Wardhani (Universitas Negeri Semarang, 2026)
Pancasila Education learning plays a strategic role in shaping students' character and creativity as part of the demands of 21st-century competencies. Along with the implementation of the Deep Learning approach, teachers are required not only to focus on mastery of content but also to foster student’s creativity. This study aims to analyze the extent to which Pancasila Education Teachers contribute to developing student’s creativity through the Implementation of Deep Learning at SMA Negeri 12 Semarang. This research employs a descriptive qualitative approach using a case study method. Data were collected through observation, interviews and documentation involving students and Pancasila Education Teachers as informants. Data validity is maintained by Triangulation Techniques, while data analysis followed the model proposed by Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The results of the research indicate that the role of Pancasila Education Teachers as designers, facilitators, and evaluators of learning is grounded in principles of Mindful, Meaningful, and Joyful learning. The implementation of discussion-based and project-based learning encourages active student engagement and the development of creativity at a conceptual level, despite experiencing obstacles in the form of differences in student characteristics, limited time, and unequal access to technology. This research emphasizes the importance of the role of teachers in bridging the implementation of Deep Learning with the development of student creativity in Pancasila Education.